2001
DOI: 10.1159/000046654
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Tuberculosis in Chronic Hemodialysis Patients

Abstract: We encountered 9 cases of tuberculosis out of our 157 chronic HD patients in 36 months. Four pulmonary, 4 lymph nodal and one isolated dermal involvement were detected. Therapy was commenced without waiting for absolute cultural or pathologic diagnosis because of the high index of clinical suspicion. All cases except one recovered completely. Among associated conditions, peptic ulcer disease, anti-HCV positivity, and diabetes mellitus were noted, though the last two did not reach statistical significance. Prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…In Turkey, the percentage of extrapulmonary tuberculosis in 2007 was 30.5% according to the report of the Ministry of Health. Extrapulmonary involvement has been reported to be high in both Turkey (38–77%) and other countries (up to 50%) among the dialysis population, 1,2,4,5,7–12 and it was 48.39% in the present study. These difficulties lead to a delayed diagnosis, sometimes postmortem.…”
Section: Discussionsupporting
confidence: 49%
“…In Turkey, the percentage of extrapulmonary tuberculosis in 2007 was 30.5% according to the report of the Ministry of Health. Extrapulmonary involvement has been reported to be high in both Turkey (38–77%) and other countries (up to 50%) among the dialysis population, 1,2,4,5,7–12 and it was 48.39% in the present study. These difficulties lead to a delayed diagnosis, sometimes postmortem.…”
Section: Discussionsupporting
confidence: 49%
“…The first report of an increased prevalence of TB in dialysis patients appeared in 1974 (2). Later, many studies, several of which are summarized in Table 1, have confirmed a 6.9‐ to 52.5‐fold increased risk of TB in patients with chronic renal failure and on dialysis as compared to the general population (3–30); an even higher risk (100‐fold) was reported from a center in London with a high immigrant population (31). Despite the well‐known association between diabetes mellitus and TB, especially pulmonary (32), only two (22,31) of the quoted studies (2–31) found a higher prevalence of TB in dialysis patients with diabetes mellitus, as compared with other renal diseases.…”
Section: Epidemiologymentioning
confidence: 98%
“…The nonspecific presenting symptoms together with the frequent extrapulmonary localization constitute risk factors for a delay in the diagnosis of TB, which unfortunately has been observed in several studies. Within the extrapulmonary group, tuberculous lymphadenitis and peritonitis are the most reported localizations; less frequently cases of military, spine (Pott's syndrome), cerebral, and genitourinary TB have been reported (2–31).…”
Section: Featuresmentioning
confidence: 99%
“…Actuellement, l'importance de la polymerase chain reaction (PCR) a été soulignée [15]. Devant cette difficulté diagnostique et la lourde mortalité liée au retard de traitement, certains auteurs préconisent un traitement d'épreuve chez les dialysés suspect de tuberculose [6,16]. Hachicha a traité 11 patients sur une simple présomption diagnostique [3].…”
Section: Discussionunclassified